2023
DOI: 10.3390/buildings13041068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Simulated Damage in Prestressed Anchorage Using Admittance-Based Active Sensing Technique

Abstract: This study examined the feasibility of the admittance-based method for detecting simulated damage in the bearing plate of a prestressed anchorage. The proposed method utilized the PZT (lead zirconate titanate) interface technique to acquire a strong admittance response from the anchorage. Firstly, the numerical feasibility of the method was demonstrated by detecting the presence of fatigue cracks and preload changes in a fixed–fixed beam-like structure. Next, the experimental verification was carried out using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Li et al [28] used embedded smart aggregates by combining EMI technology and machine learning to monitor the strength development of early-age concrete. Nguyen et al [29] examined the feasibility of the admittance-based method for detecting simulated damage in the bearing plate of a prestressed anchorage. The results indicated that structural damage leads to significant changes in the admittance spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [28] used embedded smart aggregates by combining EMI technology and machine learning to monitor the strength development of early-age concrete. Nguyen et al [29] examined the feasibility of the admittance-based method for detecting simulated damage in the bearing plate of a prestressed anchorage. The results indicated that structural damage leads to significant changes in the admittance spectrum.…”
Section: Introductionmentioning
confidence: 99%